Contemporary perspectives on research on immigration in early childhood education - Saracho, Olivia N. (Contemporary perspectives in early childhood education., 2023)
"Immigration is when individuals leave their country of residency to permanently settle in a different country. According to the United Nations (UN) Department of Economic and Social Affairs, in 2017 an cumulative of 258 million persons were residents in a country that differed from their own. The September 11, 2001, terrorist attacks and the increase in prohibited immigration impelled the United States (US) to propose a number of immigration laws. In 2012, the US Department of Homeland Security (DHS) established the Deferred Action for Childhood Arrivals (DACA) policy, which allowed undocumented immigrants to work legally without being deported as long as they maintain a useful and lawful status. Approximately 800,000 immigrants attained DACA standing, permitting them to legally work and go to school in the US. Furthermore, the immigration law of 1965 prompted an excessive entrance of multicultural immigrants to the United States which brought about a great representation of children who live with immigrant families. These children faced several environmental structures which were affected by changes and multiplicity in their family situations. Immigrant children attempted to understand a different culture, values, and emerging issues in relation to their assimilation paths. The purpose of this volume is to offer a complete representation of the way immigrant children and families respond and develop in the US and Europe. It will extend current knowledge and reinforce contemporary frameworks that associate the cultural differences between immigrant families and teachers. In the classroom environment teachers have the opportunity to effectively assume both nurturing and instructional roles to aid young children to cultivate their social and cognitive abilities. The teachers' personal characteristics, formal education, specialized training, and cultural knowledge may affect their effectiveness in the classroom environment. Most of the studies show that both family and teachers have the most significant effects on the children's development and learning. Immigration researchers and scholars are invited to review, critically analyze, discuss, and submit a manuscript for the volume titled, Contemporary Perspectives on Research on Immigration in Early Childhood Education. The concept of immigration has heavily influenced modern views in early childhood education. Researchers, scholars, and educators need to understand the current sources based on theoretical frameworks that contribute to the purposes of immigration in the United States and Europe. The contents of the volume need to reflect the major shifts in the views of early childhood researchers, scholars, and educators in relation to the research on immigration, its historical roots, the role of immigration in early childhood education, and its relationship to theory, research, and practice"--